GERMPLASM SCREENING AND INCORPORATION OF APHID RESISTANCE IN BREAD WHEAT (Triticum aestivum L.) - M. S. Wains1; M. W. Jamil1; M. A. Ali; 3; M. Hussain; J. Anwar (Journal of Animal and Plant Sciences, 2014)
The aphid infestation results in considerable crop losses in many crops. Aphids are emerging as potential insect pest to wheat crop and it might become a threat to the future wheat crop productivity in Pakistan. To cope with this serious problem, a large wheat germplasm comprising of 464 accessions of bread wheat were screened against aphids based on aphid population density during 2009-2010 in the experimental areas of Wheat Research Institute, Faisalabad. Out of 464 accessions, 71 showed an immune response having aphid population range 1-2. Similarly, 87 varieties/lines were found resistant having 3-4 aphids per tiller throughout the season. A large proportion of wheat accessions (127 accessions) supported 5-6 aphids per tiller on an average and was graded as moderately resistant, while 141 accessions were found tolerant. Small number of genotypes were tending towards susceptibility (17 were found moderately susceptible, 16 were found susceptible and 5 were found highly susceptible by showing aphid population range 7-8, 9-10, 11-15 and 16-20 respectively). Aphid resistance was successfully incorporated from aphid resistant lines into high yielding accessions through crossing followed by selection in segregating generations. Twenty crosses were made between aphid resistant and high yielding lines. Aphid population per tiller and grains yield per plant was assessed in F6 generation. The crosses from two lines viz. Faisalabad 08 and BAVICORA 92 showed the highest grain yield and aphid resistance while that of V-07200 with KAL/BB showed least grain yield and high susceptibility. The results concluded that most of the germplasm accessions are resistant to tolerant against aphids and this resistance could be incorporated into the future cultivars.
Keywords: Bread wheat; aphid population per tiller; aphid resistance; screening